The Use of the Social Network Tiktok as A Learning Tool: From Leisure to Education - Guerra , Johany Michel; Aranda, Alejandra Sofía Daza; Cruz, Tivisay Carolina Mendoza De La; Montero, Celso Nasario Albor (Journal of Ecohumanism, 2024)
This article is part of a broader study developed by the Popular University of Cesar and which aimed to investigate how the use of homework through TikTok influences the learning process of students of official educational institutions in the municipality of Valledupar, as well as the advantages and disadvantages of using this resource in the educational field. The theories of connection, connectivism and even constructivism, in supports that project the possibility of limiting concepts to carry out external operations such as the search for information, access to where to find it and/or informed in the field of education. In a recent work with Pedagogy students, I discovered a non-formal teaching support that allows another way of conceptualizing the contents of the reference subject, "Technologies for Learning Management". As can be inferred from the results of the finding, it is located where students, as digital natives, use it, not only as a leisure network, but for different categories: to be informed, to capture entertainment and learning.